The relationship between tackle technique and external load of a simulated tackle - Paul, Lara (Department of Human Biology, 2024)
Background: Monitoring players in training and matches is important to ensure players are adequately prepared for competition demands, reducing injury risk and enhancing performance. In contact sports, collision monitoring however, remains a challenge. These challenges include how to quantify the demand of specific collision events such as the tackle, and how such quantities relate to the technical aspects of the event. Coaches play an essential role in the monitoring process, however, the research on coaches in collision sports is not well understood. Objectives: The aim of this thesis is three-fold: (1) In chapter 2, the aim is to review and synthesise the current literature that quantifies collisions in rugby union and rugby sevens, (2) in chapter 3, the aim is to synthesise the current sport science and medicine literature on rugby union, rugby league, rugby sevens coaches, and (3) in chapter 4, the aim is to investigate the relationship between tackle technique and external load of a simulated tackle. Methods: For chapter 2, a systematic review and meta-analysis was completed on the frequency and intensity of collisions in rugby union and rugby sevens. For the third chapter, a scoping review was completed on coach/coaching research in rugby union, rugby league, rugby sevens. For chapter 4, 20 players performed 12 tackles (6 tackles over 2 sessions). Each tackle was recorded by three cameras and a triaxial accelerometer housed in a player unit for analysis. Following the data collection, the tackles were split into three categories – low, medium, and high scoring tackles based on their tackle technique. Results: Seventy-three studies (n = 73) were included in the final systematic review for chapter 2, with fifty-eight studies (n = 58, 79%) focusing on rugby union, and fifteen studies (n = 15, 21%) exploring rugby sevens. In rugby union, on average, a total of 22.0 (19.0 – 25.0 95%CI) scrums, 116.2 (62.7 – 169.7 95%CI) rucks, and 171.2 (140.5 - 201.8 95%CI) tackles occur per match. In sevens, on average 1.8 (1.7 – 2.0 95%CI) scrums, 4.8 (0 – 11.8 95%CI) rucks and 14.1 (0 – 32.8 95%CI) tackles occur per match. In chapter 3, a total of one hundred and one articles(n = 101) were included in the final review, which included a sum of 4233 participating coaches. The three main themes identified were Coach knowledge (n = 68, 68%), Coach pedagogies (n = 29, 29%) and Coach development (n = 4, 4%). For the study chapter, Power of the shoulder and PlayerLoadTM at contact were significantly higher at contact for higher scoring tackles (low scoring tackles: 7.9 (5.3 - 10.5 95%CI) kW versus high scoring tackles: 27.8 (11.36 - 44.3 95%CI) kW). PlayerLoadTM at contact also had the highest relative importance for tackle technique (Gini index: 25.4). Conclusion: Per minute, rugby sevens players performed more tackles than rugby union players and forwards experienced more impacts and tackles than backs. The frequency and intensity of collisions in training and matches may lead to adaptations for a “collision-fit” player and lend itself to general training principles such as periodisation for optimum collision adaptation. When analysing the coaches' research, there is a positive trend in coach's knowledge of injuries, specifically concussions. Moving forward, continual practical educational input should be provided for our coaches to protect the welfare of our rugby players. Another finding was a shift from coach-centred learning to playercentred learning. Although, coaches are reluctant for this change it helps develop players to make their own decisions and read the game for themselves. When comparing differences in external load and tackle technique, the results suggest that players in the optimum position in the tackle at contact is suggested to produce more power of the shoulder and PlayerLoadTM. Although, players produce higher force in the lower scoring tackles, it can be suggested that they are not executing the force in the correct way or place. PlayerLoadTM has been shown to be an important variable when monitoring tackle technique. Using external load measurements along with tackle technique assessments allows coaches to understand the dynamic nature of the tackle further resulting in the ability to optimise tackle training, monitor contact and preparing players for competition.